Large disparities in 28‐day case fatality by stroke subtype: data from a French stroke registry between 2008 and 2017. (3rd May 2021) - Gauthier, Victoria; Cottel, Dominique; Amouyel, Philippe; Dallongeville, Jean; Meirhaeghe, Aline
Abstract: Background and purpose: The objectives of the present analysis were to assess 28‐day stroke case fatality according to the stroke aetiology and to identify associated factors. Methods: All stroke events in adults aged ≥35 years between 2008 and 2017 were collected in a population‐based stroke registry in northern France. Results: Out of a total of 2933 strokes, there were 479 (16%) haemorrhagic strokes and 2454 (84%) ischaemic strokes; the 28‐day case fatality rates were 48% and 15%, respectively. Three‐quarters of the 28‐day case fatalities occurred within 6 days of the event for haemorrhagic strokes and within 16.5 days for ischaemic strokes. After an ischaemic stroke, the case fatality rate was higher for women (18%) than for men (12%, p  < 0.0001); however, this difference disappeared after adjustment for age. Cardioembolic strokes (34%) and strokes of undetermined cause (33%) were the most common ischaemic subtypes, with case fatality rates of 16% and 18%, respectively. Large artery atherosclerosis (11%) and lacunar strokes (10%) were less common, and both types had a case fatality rate of 3%. Age at the time of the event and stroke severity were both significantly associated with case fatality. For some types of stroke, a history of cardiovascular events and residence in a nursing home were associated with a poor prognosis. Medical care in a neurology ward was inversely associated with case fatality, for all stroke subtypes. Conclusions: In northern France, post‐stroke case fatality remains high, especially for haemorrhagic stroke. Being treated in a neurology ward improved survival by around 80%.